Akibat Hukum Budaya Kad’di Dalam Adat Masyarakat Sabu - Chatryen M Dju Bire; Herman Elfridus Seran; Jenny Ermalinda (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2023)
In relation to marital problems, if an incident occurs where the husband dies first, the culture of Kad'di must be applied.  Culture is Kad'di carried out when the husband dies where the husband's body has been buried. When the wife returns to her original clan, important things arise, including the management of children and property problems. Likewise, if the children left behind are immature, problems will arise, namely who or which party is responsible for guiding and caring for them. Then in relation to the issue of marital property. This is what makes researchers interested in conducting research with the title "The Impact of the Cultural Law of Kad'di in the Customs of the Sabu Community". So the purpose of this study is to see the legal consequences of the occurrence of Kad'di both the legal consequences for children and the legal consequences of Kad'di on property. The results of the study show that the legal consequences arising from Kad'di itself for children are the legal consequences of shifting the management of children from the wife/widow to the family of the deceased husband which has psychologically affected the children. While the legal consequences of the occurrence of Kad'di on the property where the widows are not the heirs of the ex-husband's side because of that the widows do not have the right to the inheritance, including the joint property of her late ex-husband.